(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The habitual consumption of gutkha, a smokeless form of tobacco containing areca nut and slaked lime, is a pervasive and concerning practice in many regions of the world, particularly in South Asia. This study presents an overview of the comprehensive research conducted to unravel the intricate relationship between gutkha consumption and its profound impact on periodontal health and oral hygiene. Gutkha’s composition, which includes tobacco, areca nut, slaked lime, and various additives, contributes to its highly addictive nature. This habit has been associated with a myriad of adverse oral health consequences. The present research synthesizes findings from numerous epidemiological studies, clinical trials, and in vitro experiments, collectively suggesting that gutkha consumption significantly elevates the risk of periodontal diseases, including gingivitis and periodontitis. The presence of tobacco and areca nut in gutkha exposes the oral cavity to various carcinogens, further increasing the vulnerability of gutkha users to oral cancer. In addition to periodontal health, the studies explored in this research highlight the harmful effects of gutkha on oral hygiene. Gutkha’s constituents contribute to the formation of dental plaque and calculus, promoting the growth of pathogenic bacteria and leading to bad breath, tooth discoloration, and dental decay